PENERAPAN GOOD POLITICAL GOVERNANCE SEBAGAI UPAYA TRANSPARANSI DANA PARTAI POLITIK - Malia, Evi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
All Political Parties have fulfilled the Receipt and Use of Campaign Funds (LPPDK) reports, because if they are not fulfilled, they will get sanctions based on KPU Regulations. The preparation of these various reports shows that political parties are obliged to demonstrate good governance to the public, in order to form a stigma that political parties have high accountability with a high level of transparency. However, in reality this is not directly proportional to the daily governance of political parties. This study uses a qualitative research method with an interpretive approach, where data collection uses data triangulation. As for the results of the research, namely the rules that cover political parties are clear, but their application has not been implemented as the existing legal umbrella, namely law. Unlike the case with the implementation of elections related to campaign funds. Realizing good political party governance must start from the awareness of party officials to always present data and reports in a transparent manner, not only obeying during elections but continuously and continuously. Not only afraid of direct sanctions imposed by the KPU, but also pay attention to the continuity and sustainability of political parties. Going concern does not only apply to business entities, but it is also important to apply to political party organizations. Political parties are a gathering place for cadres who become and or will still be public officials who later carry out the mandate and work for the people, this is the reason for the importance of accountability and transparency for good party governance.